2019
DOI: 10.1186/s12879-019-4626-7
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of group B streptococcus ST17 hypervirulent clone among non-pregnant patients from a Hungarian venereology clinic

Abstract: BackgroundAlthough Streptococcus agalactiae is the leading causative agent of neonatal sepsis and meningitis, recently it is increasingly isolated from non-pregnant adults. The relation between its presence in the genitourinary tract and manifested clinical symptoms of STD patients remains an open question. In this study, a complex epidemiological investigation of GBS isolates from a venerology clinic was performed.MethodsNinety-six GBS isolates were serotyped and their genetic relatedness determined by PFGE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
1
11
1
2
Order By: Relevance
“…In the current study, CPS type V was shown to be the most homogenous type. The obtained finding is probably the result of its clonal propagation which is in accordance with previously published reports [35][36][37] . Interestingly, based on the PFGE banding patterns, genotype III/ST17 was less homogenous.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, CPS type V was shown to be the most homogenous type. The obtained finding is probably the result of its clonal propagation which is in accordance with previously published reports [35][36][37] . Interestingly, based on the PFGE banding patterns, genotype III/ST17 was less homogenous.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, based on the PFGE banding patterns, genotype III/ST17 was less homogenous. The obtained finding led to the hypothesis that PFGE may distinguish different ST17 lineages 37,38 . Expectedly, the PFGE analysis showed that Table 3.…”
Section: Discussionmentioning
confidence: 92%
“…High prevalence (61.54%) of these strains was isolated in rectal and vaginal samples from pregnant women approaching childbirth. This result is higher than those reported by Kardos et al (2019) on strains isolated from non-pregnant women. The high prevalence of this strain could be linked to the dissemination of the same clone in southern Benin and a characterization based on the MLST method of the strains could help to better understand this high rate in the population of pregnant women.…”
Section: Genes Of Resistance To Mlsb P-value Ermb (%) Ermtr (%) Mef(a/e) (%)contrasting
confidence: 72%
“…The hvgA gene connected to the highly virulent ST17/CC17 clone that enables persistent colonization by GBS and contributes to meningitis in neonates (Alhhazmi et al, 2016;Burcham et al, 2019;Kardos et al, 2019) was not found in our strains, except the serotype III reference strain, which belongs to the highly virulent ST17 clone (Supplementary Table 1). Both the scpB and lmb genes were generally detected together in the majority of the isolates in this study (Table 1).…”
Section: Discussionmentioning
confidence: 86%